Silver nanoparticles embedded in zeolite membranes: release of silver ions and mechanism of antibacterial action - Nagy A (Dove Medical Press, 2011)
Amber Nagy1, Alistair Harrison2, Supriya Sabbani3, Robert S Munson, Jr2, Prabir K Dutta3, W James Waldman11Department of Pathology, The Ohio State University; 2Center for Microbial Pathogenesis, Research Institute at Nationwide Children's Hospital, 3Department of Chemistry, The Ohio State University, Columbus, OH, USABackground: The focus of this study is on the antibacterial properties of silver nanoparticles embedded within a zeolite membrane (AgNP-ZM).Methods and Results: These membranes were effective in killing Escherichia coli and were bacteriostatic against methicillin-resistant Staphylococcus aureus. E. coli suspended in Luria Bertani (LB) broth and isolated from physical contact with the membrane were also killed. Elemental analysis indicated slow release of Ag+ from the AgNP-ZM into the LB broth. The E. coli killing efficiency of AgNP-ZM was found to decrease with repeated use, and this was correlated with decreased release of silver ions with each use of the support. Gene expression microarrays revealed upregulation of several antioxidant genes as well as genes coding for metal transport, metal reduction, and ATPase pumps in response to silver ions released from AgNP-ZM. Gene expression of iron transporters was reduced, and increased expression of ferrochelatase was observed. In addition, upregulation of multiple antibiotic resistance genes was demonstrated. The expression levels of multicopper oxidase, glutaredoxin, and thioredoxin decreased with each support use, reflecting the lower amounts of Ag+ released from the membrane. The antibacterial mechanism of AgNP-ZM is proposed to be related to the exhaustion of antioxidant capacity.Conclusion: These results indicate that AgNP-ZM provide a novel matrix for gradual release of Ag+.Keywords: silver nanoparticles, zeolite, antibacterial agent, oxidative stress